First record of fossil Priacma (Coleoptera: Archostemata: Cupedidae) from the Jehol Biota of western Liaoning, China - Tan, Jing J.; Ren, Dong; Shih, Chung K. (Zootaxa, 2006)
Four new fossil species of the genus Priacma, P. latidentata sp. nov., P. tuberculosa sp. nov., P. clavata sp. nov. and P. renaria sp. nov., are described from the Yixian Formation of western Liaoning, China. This finding documents the first record of fossil Priacma in China and extends the geographical distribution of this genus.